KOMUNIKASI PENGASUHAN NEUROSAINS DALAM KOMUNIKASI PENGASUHAN - Nur Armiyati; Mardiana; Salwa Arisanti; Astira Sri Rahayu; Evarastina; Herman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The brain is the center of human intelligence that controls the nervous system incapturing learning. Early childhood education through a neuroscience approachcan be implemented through various methods, including by providing educationfirst and must understand the performance of the human brain. In addition, it alsopays attention to the natural work of the brain of students in the learning process.The purpose of this paper is to describe the importance of understanding theneuroscience approach for early childhood in the learning process. This articleexplores how neuroscience principles can be used to design teaching methodsthat are more effective and in accordance with childrens cognitive development.Neuroscience-based learning emphasizes the balance of the use of various partsof the brain, not just the logically oriented left brain. Although there are challengesin applying scientific findings to educational practice, a deep understanding ofneuroscience can create a learning environment that supports childrens holisticgrowth. Thus, this paper aims to strengthen the relevance of neuroscience inimproving the quality of early childhood post-education.